Egg Yolk Fatty Acids, Blood Parameters and Some Reproductive Measurements of Japanese Quail Supplemented with Chia Seeds (Salvia hispanica L.) - Ahmed , Suad Kh. (International Journal of Poultry Science, 2019)
Background and Objective: This study was conducted to investigate the effect of supplementing Japanese quail hens with plant sources of omega-3 fatty acids on blood and reproductive traits and egg fatty acid profiles. Materials and Methods: A total of 240 female Japanese quail, 48 days old, were randomly distributed into 4 treatments with 3 replicates per treatment, as follows: T1 was the control and was without any addition and T2, T3 and T4 were supplemented with 4, 8 and 12 g chia seeds/kg diet, respectively. Results: The statistical analysis showed that T3 significantly reduced the blood uric acid, glucose, LDL, triglycerides and VLDL, while the PCV, Hb, total protein, albumin (A), globulin (G), A/G ratio, cholesterol and calcium were not affected significantly by the supplementation treatments. The egg formation hormones estrogen, follicle stimulating hormone (FSH) and luteinizing hormone (LH) increased significantly (p